Penatalaksanaan Isolasi Mandiri Pada Pasien Covid-19 - Eppy Setiyowati; Mulyadi Mulyadi; Umi Hanik; Arief Candra Purnama; Anis Muthaharoh; Sri Wilujeng; Madjid Madjid; Ami Ardianti (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The increase in covid 19 sufferers in some areas has increased quite significantly even deaths due to the transmission of the covid19 virus is a pandemic that is sweeping several countries including one in Indonesia. The purpose of the devotional activity is to provide health education about self-isolation treatment protocols in COVID-19 patients at dr Ramelan Hospital polyclinics Surabaya. This approach in community service is to conduct health education by playing a video that contains about self-isolation treatment protocols in covid 19 patients. This event is held for 2 weeks (July 25 to August 10, 2021). The final result of community service activities is an article published in a national journal and recorded in the form of learning media, namely videos and titles on patented banners (HaKI).